Is Less Surgical Treatment Possible in the Treatment of Degenerative Spine Diseases? Four-Year Follow-up Results of Foraminal Epidural and Facet Joint Injection Treatments - Uğur Ertem (Genel Tıp Dergisi)
In this article, I would like to share my opinions about the article named 'Is Less Surgical Treatment Possible in the Treatment of Degenerative Spine Diseases? Four-Year Follow-up Results of Foraminal Epidural and Facet Joint Injection Treatments' (1). First of all, I would like to thank the authors. I will especially try to contribute to this article from the perspective of a physical medicine and rehabilitation physician.